The Extent to Which Financial Institutions Comply With The US FATCA Law - Murad, Khairi Ibrahim (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article explores the challenges and risks faced by Iraqi banks in complying with the Foreign Account Tax Compliance Act (FATCA). The study aims to investigate the extent of compliance in Iraqi banks and examine the general framework of FATCA through document analysis and interviews with bank officials. The results reveal that while Iraqi banks encounter various challenges in adhering to FATCA, they are actively taking significant steps to implement the necessary changes. The study highlights the need for continued monitoring of compliance efforts and emphasizes the importance of adapting to the global banking system. The implications of this research underscore the crucial role of FATCA in preventing tax evasion and ensuring tax compliance among US taxpayers utilizing non-US financial institutions and investment vehicles abroad. This research contributes valuable insights for professionals in the field, policymakers, and researchers interested in understanding the impact of FATCA on the banking sector and its implications for global financial regulations. Highlights : Challenges and risks faced by Iraqi banks in complying with FATCA. Active steps taken by Iraqi banks to implement necessary changes for FATCA compliance. Implications for preventing tax evasion and ensuring tax compliance in the global financial landscape. Keywords : FATCA Compliance, Iraqi Banks, Tax Evasion, Global Banking System, Financial Regulations